2009
DOI: 10.1021/pr900743b
|View full text |Cite
|
Sign up to set email alerts
|

A P4-ATPase Protein Interaction Network Reveals a Link between Aminophospholipid Transport and Phosphoinositide Metabolism

Abstract: High-throughput analysis of protein-protein interactions can provide unprecedented insight into how cellular processes are integrated at the molecular level. Yet membrane proteins are often overlooked in these studies owing to their hydrophobic nature and low abundance. Here we used a proteomicsbased strategy with the specific intention of identifying membrane-associated protein complexes. One important aspect of our approach is the use of chemical cross-linking to capture transient and lowaffinity protein int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
0
13
0
2
Order By: Relevance
“…Genetic associations with drs2 have been described for ADP-ribosylation factors (recruitment of coat protein complexes) and Rab proteins [54,9092]. Using tandem-affinity purification and mass spectrometric analyses, Puts et al have identified additional Drs2p-interacting proteins with a role in vesicular trafficking [91]. Amongst others, three proteins involved in phosphoinositide metabolism were identified, including a PI4P phosphatase.…”
Section: P4 Atpases and Vesicular Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic associations with drs2 have been described for ADP-ribosylation factors (recruitment of coat protein complexes) and Rab proteins [54,9092]. Using tandem-affinity purification and mass spectrometric analyses, Puts et al have identified additional Drs2p-interacting proteins with a role in vesicular trafficking [91]. Amongst others, three proteins involved in phosphoinositide metabolism were identified, including a PI4P phosphatase.…”
Section: P4 Atpases and Vesicular Transportmentioning
confidence: 99%
“…In addition, the different subcellular distributions of the newly identified Drs2p-interacting proteins ( i.e. , Golgi apparatus (GA), ER, plasma membrane, and vacuole) suggest that Drs2p resides in different protein complexes within distinct trafficking pathways [91]. …”
Section: P4 Atpases and Vesicular Transportmentioning
confidence: 99%
“…For instance, amino acids required for cross-linking are rather rare in hydrophobic domains. Yet, cross-linking may stabilise the interaction between soluble and membrane-embedded subunits, supporting their combined isolation (Puts, Lenoir, Krijgsveld, Williamson, & Holthuis, 2010). Anyway, an examination of at least the hydrophilic stretches of membrane subunits and of the associated solventexposed subunits should be feasible (Fig.…”
Section: Falick and Komivesmentioning
confidence: 98%
“…The yeast P4-ATPases Drs2p and Neo1p were found to interact with cytosolic proteins such as guanine nucleotide exchange factors and small GTPases that are crucial for the recruitment of coat proteins during membrane budding [7, 11, 15, 31, 92, 102]. Furthermore, a systematic search for Drs2p-binding partners yielded proteins involved in phosphoinositide metabolism [70]. Phosphoinositides are important signaling molecules in membrane traffic that help establish organelle identity through recruitment of effector proteins.…”
Section: Physiological Implications Of P4-atpase-catalyzed Phospholipmentioning
confidence: 99%